Efficacy of Mandibular 2-implant Overdenture: An Updated Meta-analysis on Patient-based Outcomes. (April 2016) - Kodama, N.; Singh, B.P.; Cerutti-Kopplin, D.; Feine, J.; Emami, E.
The extent of heterogeneity regarding the efficacy of the mandibular 2-implant overdenture is still in question. The aim of this meta-analysis is to provide an update on the existing evidence from randomized controlled trials assessing the efficacy of the mandibular 2-implant overdenture in regard to patient-based outcomes. Electronic searches were carried out to September 2015 through MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, and the Cochrane Systematic Reviews. Only randomized controlled trials that compared conventional dentures with mandibular 2-implant overdentures were included. Patient-based outcomes were assessed, including patient satisfaction and oral health– and general health–related quality of life. Random effects models were used to pool the effect sizes of all included studies. Further stratified analyses and heterogeneity analyses were tested, as was publication bias. In addition to the 7 randomized controlled trials that were included in the previous meta-analysis, 4 new trials were identified and included in this update. A random effects model showed that, when compared with conventional dentures, mandibular 2-implant overdentures significantly improved patient satisfaction (pooled effect size = 0.87, z = 5.31, 95% confidence interval: 0.55 to 1.19, P < 0.0001, χ 2 = 41.82, df = 8, P < 0.0001, I 2 = 81%) and oral health–related quality of life (pooled effect size = −0.66, z = 2.72, 95% confidence interval: –1.13 to −0.18, P = 0.007, χ 2 = 21.26, df = 4, P = 0.0003, I 2 = 81%). The differences in participant recruitment and their pretreatment condition were important sources of heterogeneity among the studies. Only 1 study investigated the impact of mandibular implant overdentures on perceived general health, and it revealed no between-treatment differences. The 2-implant mandibular overdenture improves patient satisfaction and quality of life for the general edentate population. Health status, poor oral condition, and patient characteristics may effect patient-based outcomes and should be considered by clinicians in treatment planning. Knowledge Transfer Statement : This meta-analysis shows that mandibular 2-implant overdentures are significantly more satisfactory to the general edentate populations than new conventional dentures. The results also show that mandibular 2-implant overdentures provide significantly better oral health–related quality of life than do new conventional dentures. These results should be shared with edentate patients in planning their treatment.